2015
DOI: 10.1021/jacs.5b06656
|View full text |Cite
|
Sign up to set email alerts
|

Transannular [6 + 4] and Ambimodal Cycloaddition in the Biosynthesis of Heronamide A

Abstract: The transannular [6 + 4] cycloaddition proposed as a step in the biosynthesis of heronamide A has been modeled using density functional theory. The proposed cycloaddition is highly stereoselective, affording a single product. The reaction proceeds through an ambimodal transition state that directly leads to a [4 + 2] adduct in addition to the observed [6 + 4] adduct. Interconversion of these adducts is possible via a facile Cope rearrangement. The [6 + 4] adduct is thermodynamically more stable than the [4 + 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 45 publications
2
83
0
1
Order By: Relevance
“…A bifurcating reaction is a reaction in which a single transition state connects the reactant(s) and two different products (Figure (b)) through a bifurcation point (more precisely, a valley‐ridge inflection (VRI) point) on the potential energy surface (PES) . Many examples of bifurcating reactions have been studied by Houk and his co‐workers . However, it remains a difficult task to identify whether a reaction is a bifurcating reaction or not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A bifurcating reaction is a reaction in which a single transition state connects the reactant(s) and two different products (Figure (b)) through a bifurcation point (more precisely, a valley‐ridge inflection (VRI) point) on the potential energy surface (PES) . Many examples of bifurcating reactions have been studied by Houk and his co‐workers . However, it remains a difficult task to identify whether a reaction is a bifurcating reaction or not.…”
Section: Resultsmentioning
confidence: 99%
“…Two cluster compounds discussed in main text were calculated using PBE0 with a large def2TZVP basis set (along with associated pseudopotentials if present) for all atoms. Singlet point calculations were performed for the transition states of the bifurcating reaction with the geometries provided in the original work done by Houk's group using the same computational method (M06‐2X/6‐311++G(d,p)) . NAOs are obtained using NBO6.0 software .…”
Section: Methodsmentioning
confidence: 99%
“…At some specific point, however, the valley branches at the bifurcation before any transition state is reached and two new valleys with their own subsequent transition states, labeled as TS 1 and TS 2 in Figure (b), emerge. Although downhill bifurcations are, for instance, well‐established in the realm of thermal cycloaddition reactions, uphill bifurcations are far less frequently described in the extant literature . Indeed, this rare topological phenomenon has not been addressed at all in recent authoritative overview articles on reaction path bifurcations, whereas a rigorous definition can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, these data beg the question: Can an enzyme control the outcome of an ambimodal reaction by altering the energy surface such that the steepest downhill path from the transition state leads to the “desired” product(s)? Tantillo et al have suggested that this sort of dynamic selection plays a role in terpene biosynthesis 21a Such possibilities are entirely distinct from the lowering of reaction barriers that is assumed to completely define catalysis, but they are recognizable when the dynamic complexity of real reactions. Hoye et al have demonstrated that a biomimetic Diels–Alder reaction is ambimodal.…”
mentioning
confidence: 99%
“…Hoye et al have demonstrated that a biomimetic Diels–Alder reaction is ambimodal. 21b Recently, a related ambimodal [6+4] cycloaddition was implicated in the biosynthesis of heronamide A, but in this case the [6+4] adduct was found to be more thermodynamically stable than the isomeric Diels–Alder product. 21c …”
mentioning
confidence: 99%